Improvement of Electric Power Generation at Khor Al- Zubair Gas Turbine Power Plant by Using Vapor Compression Cooling Cycle - Faisal, Safaa Hameed; Ateeq, Adnan Abdulla; Ali, Hanadi Mahmood (Basrah Journal for Engineering Sciences, 2019)
In this work, both energy and exergy analyses have been carried out on General Electric (GE) gas turbine unit found in Khor Al-Zubair gas turbine power plant located in Basra, Iraq. The analysis covers the ISO (international standards organization) operating conditions in addition to actual operating data recorded for one month in hot season July 2016. The feasibility of adopting a vapor compression cycle (VCC) for cooling the intake air is evaluated. Generally, the study reveals an obvious drop off for most plant performance characteristics while operating during the hot season. Energy and exergy analyses show that adopting the vapor compression cycle to enhance Khor Al-Zubair GE unit could improve the power output by 20% and 27% in case of part-load and full-load conditions respectively. Both of first and second law efficiencies could be improved by 3.5% at part- load and 9% at full load. The expected cooling load needed for the unit is in the range of 2697 to 3024.5 TR according to part- load and full-load operation respectively. Only total irreversibility of the unit is expected to increase in case of adopting VCC and this will not impair the improvement in second law efficiency of the unit. Among the unit components, combustion chamber has the largest computed irreversibility. Further improvement is recommended by utilizing the released heat energy to the atmosphere, which is characterized by significant work potential.